2018
DOI: 10.47203/ijch.2018.v30i03.016
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological Study on Burden of Psychological Morbidities and Their Determinants among Undergraduate Medical Students of a Government Medical College of Eastern India

Abstract: Background: Medical education can impose a significant amount of psychological stress and strain on undergraduates. In India, there are limited shreds of evidence regarding the magnitude of different psychological morbidities (i.e. stress, anxiety and depression) among medical undergraduates. Aims & Objectives: To find out the proportion of medical undergraduates suffering from psychological morbidities and their determinants. Material and Methods: It was a cross-sectional hospital-based analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
2
1
1
Order By: Relevance
“…19,26 The observation of the present survey demonstrated that socio-demographic variables such as age and substance consumption behavior were statistically significant between the comparable groups with psychological morbidities. These results were nearly similar to the observations of few studies done by Mangalesh et al 9 and Biswas et al 35 in which psychological morbidities among different years of UGs training were statistically significantly associated with age, gender, living status, and substance consumption behavior. Zvauya et al 21 and Kiran et al 32 also found that psychological morbidities among pre-/para-clinical and clinical UGs were statistically significantly associated with age of the participants.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…19,26 The observation of the present survey demonstrated that socio-demographic variables such as age and substance consumption behavior were statistically significant between the comparable groups with psychological morbidities. These results were nearly similar to the observations of few studies done by Mangalesh et al 9 and Biswas et al 35 in which psychological morbidities among different years of UGs training were statistically significantly associated with age, gender, living status, and substance consumption behavior. Zvauya et al 21 and Kiran et al 32 also found that psychological morbidities among pre-/para-clinical and clinical UGs were statistically significantly associated with age of the participants.…”
Section: Discussionsupporting
confidence: 91%
“…These findings align with previous research in the literature which reported that dissatisfaction with academic performance was one of the key factors in inducing the mental health issues among medical students. 9 35 43 44 In the present survey, it was also highlighted that students in the clinical group were more in proportion with dissatisfied academic performance than the pre-/para-clinical group, validating the already existing findings where dissatisfaction with academic performance proportionally increased with advancement in phase training. 15 This could possibly be due to self-perceived lack of knowledge in clinics, and insecurities about clinical competencies and future careers, leading to fear of failure in exam, due to which students might have feelings of worthlessness, hopelessness, and uselessness that ultimately lead to multiple mental health issues.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations